Resorts by Thai architects : serene modernity - Sthapitanonda, Nithi (Singapore : Page One Publishing Pte Ltd., 2012)
Resorts by Thai Architects, first published in 2009, compromised of eight projects by eight architects. All of the works demonstrated unique site specific design solutions that blended the resorts with the existing surroundings and local architecture. Each architect succeeded in finding the right answer for each project, both physically and economically. As a result, they gained a good reputation and many visitors to their projects.
Preface -- Introduction -- Sala Khaoyai (Onion) -- Muthi Maya Forest pool Vila (Anupap design practice) -- Asara Vila and Suite (KTGY inter-associates) -- X2 Resort Jui Buri (Duangrit Bunnag Architect) -- Le Meredien Samui (Begray) -- Dri Panwa Phuket (Habita) --Veranda Chiangmai The High Resort (The Office of Bangkok Architects) -- Phulay Bay A Ritz Carlton Reserve (Bunnag Architects) -- Biography.
Keywords: ARCHITECTS -- THAILAND